Application of the Arch of Maguerez in the dressing room of a Basic Health Unit: experience report (Research, Society and Development, 2022)
Objective: to report the experience of applying the Arc of Maguerez in the organization of the dressing room in an objective, effective and easy-to-follow way for the professionals of the nursing teams of a basic health unit. Method: experience report through the Arc of Charles Maguerez, in the perspective and adaptation of Berbel. Results and discussion: Applied the five stages of the Arc of Maguerez. In which the impacts that the lack and disorganization of materials generate in care practice were observed; key points were raised; after critical reflection, a search was carried out for safe information that provided theoretical support; and proposed hypotheses to solve the problem with its subsequent application to reality. Conclusion: The present study allowed us to report a successful experience in the context of the organization of nursing services in a basic health unit in the Federal District supported by the Active Methodology.